Effects of in vivo treatment of mice with sulforaphane on repair of DNA pyridyloxylbutylation. (30th April 2021) - Harris, Christopher M.; Zamperoni, Kristen E.; Sernoskie, Samantha C.; Chow, Natalie S.M.; Massey, Thomas E.
Highlights: Increased DNA repair is a novel chemoprotective action of sulforaphane (SF). SF increases hepatic bulky DNA adduct repair activity in vivo . Increased hepatic repair activity is consistent with activation of Nrf2 signaling. In vivo SF treatment does not alter histone H3 acetylation. In vivo SF treatment does not induce DNA damage. Abstract: The phytochemical sulforaphane (SF) has gained interest for its apparent association with reduced cancer risk and other cytoprotective properties, at least some of which are attributed to activation of the transcription factor Nrf2. Repair of bulky DNA adducts is important for mitigating carcinogenesis from exogenous DNA damaging agents, but it is unknown whether in vivo treatment with SF affects adduct repair. At 12 h following a single oral dose of 100 mg/kg SF, an almost doubling in activity for repair of pyridyloxobutylated DNA was observed in CD-1 mouse liver nuclear extracts, but not in lung extracts. This change at 12 h in repair activity was preceded by the induction of Nrf2-regulated genes but not accompanied by changes in levels of the specific nucleotide excision repair (NER) proteins XPC, XPA, XPB and p53 or in binding of hepatic XPC, XPA and XPB to damaged DNA. SF also did not significantly alter histone deacetylase activity as measured by acetylated histone H3 levels, or stimulate formation of γ-H2A.X, a marker of DNA damage. A significant reduction in oxidative DNA damage, as measured by 8-OHdG (a biomarker of oxidative DNA damage), was observed only in DNA from the lungs of SF-treated mice 3 h post-dosing. These results suggest that the ability of SF to increase bulky adduct repair activity is organ-selective and is consistent with activation of the Nrf2 signaling pathway.